Capital punishment or capitol forgiveness? The enduring message of Dead Man Walking - Frederick Hale (Acta Theologica)
The best-selling book and internationally popular film Dead Man Walking address squarely the issue of capitol punishment which has been extensively debated throughout much of the world and challenged the ethical thinking of Christian and non-Christian moralists. Although this question is treated in Dead Man Walking in an explicitly Roman Catholic context in the United States of America, the ethical and spiritual dimensions of its treatment on the screen transcend geographical and denominational borders and are particularly relevant to South Africa, where escalating violence in recent years has engendered a callousness and spirit of vengefulness in many quarters and where public support for the death penalty is strong.